THE INFLUENCE OF ELECTRONIC WORD OF MOUTH, SECURITY, AND TRUST ON PURCHASING DECISIONS ON TOKOPEDIA MARKETPLACE IN BATAM CITY - Agustina, Agustina; Wasiman, Wasiman (Universitas Muhammadiyah Tangerang, 2024)
Tokopedia marketplace visitors have decreased in each period, namely from the second quarter of 2022 with a total of 158,300,000 visitors to the third quarter of 2023 with a total of 97,066,667 visitors, this can happen due to certain factors that can influence the purchase decision of the Tokopedia marketplace. The purpose of this study is to find out whether there is an influence of E-wom, Security, Trust and Purchasing Decisions. Quantitative research method with Jacob Cohen's formula which total of respondents 204 people. Purposive sampling technique using data collection method is distributing questionnaires with Likert scale measurement. This study uses multiple linear regression analysis with the results of E-wom, Security and Trust has a positive and significant influence on the Tokopedia Marketplace in Batam City.